Human Rights at the United Nations: In a Tension Between Universality and Ambivalence - Marguerite A. Peeters (Chrześcijaństwo-Świat-Polityka)
This paper analyzes the tension, within the context of the United Nations, between the proclaimed universality of human rights since 1948 and the progressive destabilization of their core content, in a dramatic momentum since 1968. The paper identifies key milestones in this process. It uses a historical approach revisiting the context in human rights integrated the UN mandate and were later interpreted at major international conferences, focusing on the leadership of feminist individuals and lobbies. It relates the tension between universality and ambivalence to a conflict between two opposed anthropological perspectives, viewing the human being either as a person endowed with a given nature, or as an individual with the power to freely choose how to construct itself. Those upholding the former view may not always have reached as clear a consensus as generally assumed on the very concept of person. The way forward may be to complete the past anthropological underpinnings of universal human rights with the development of an ontology of love.